M MISI KEADILAN PERSPEKTIF ENSIKLIK FRATELLI TUTTI - Maksimilianus Petong Nalut; Egidius Agu (Jurnal Pelayanan Pastoral, 2024)
Injustice is a complex problem in various fields of human life. The Catholic Church, with its mission as a propagator of moral values and humanity, has a crucial role in creating justice in society. Pope Francis, through the Encyclical Fratelli Tutti, calls for the importance of justice missions based on universal brotherhood in facing the world's injustice crisis. The call to brotherhood transcends the barriers of faith and culture, striving for true humanity. The purpose of this study is to analyze the mission of justice in the view of Fratelli Tutti to answer the challenges of global injustice. It also seeks to explore how the Church applies the messages in Fratelli Tutti in their daily lives, both personally and socially, to create positive changes in society. The methods used in this research are qualitative methods and critical reading of the encyclical as well as analysis of related literature. The result of this research is that the mission of justice carried out by the Church in its ministry should be carried out in the spirit of universal brotherhood, which includes the face of love, the spirit of dialogality, and actions as ambassadors of justice who are brave and committed to fighting for justice every day. This mission of justice is not only a legal demand, but also a divine call and moral call for the Church to act as an agent of renewal that brings society to a better place. In addition, the mission of justice is also not only about giving appropriate punishment to perpetrators of injustice, but also about reconciliation. The Church, through this role, can realize its humanity in the midst of a world and society that experiences injustice. The research findings are that the mission of justice promoted by the encyclical can answer the challenges of global injustice, build social change, and repair broken relationships. It is this inclusive and just attitude that will move people to fight for social justice.